Quantification and Reproducibility of Tracking Cortical Extent of Activation by Use of Functional MR Imaging and Magnetoencephalography - P.L. Roberts, Timothy (AJNR Am J Neuroradiol, 2000)
BACKGROUND AND PURPOSE: Functional MR imaging and magnetoencephalography are commonly used to study normal cortical sensory and cognitive processing as well as a variety of disease states. The usefulness of these techniques is dependent on the reproducibility and sensitivity to change of derived measures of brain function. The purpose of this study was to compare the efficacy of functional MR imaging and magnetoencephalography as measures of the extent of cortical activity in response to a graded stimulus. METHODS: Five participants underwent functional MR imaging and magnetoencephalography involving stimulation of one, two, three, and four digits of the left hand. Measurements of activation were repeated three times per participant. The cortical extent of activation was assessed for functional MR imaging by observing the number of “activated” pixels and the “amount of activation”: the product of the number of activated pixels and the mean signal change. Activation was quantified for magnetoencephalography as the magnitude of the evoked magnetic field peak and as the strength of the modeled current source, Q. RESULTS: For functional MR imaging, the number of activated pixels tended to increase with the increasing number of stimulated digits. High intra- and interparticipant variability (66% and 85% variation, respectively) did not, however, allow statistical resolution of this trend. The amount of activation was similarly variable (interparticipant, 89%). Magnetoencephalography was more robust regarding quantification. The evoked field amplitude varied linearly with the number of digits stimulated; intra- and interparticipant variability was 18% and 41%, respectively, permitting resolution of significant differences between any combination of stimulated digits, except two versus three (P < .05). CONCLUSION: Although functional MR imaging and magnetoencephalography show measurable evoked responses with somatosensory stimulation, in this study, functional MR imaging did not permit robust quantification of increasing cortical areas of activation.